Islam Jawa: Dari mitis ke Epistemologis - Agnesius, Marselus (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2007)
Before the coming of Islam, Javanese society was and is still - very much coloured by Hinduism, Buddhism and local religious believes. It formed some sort of religious syncretism. Islamic teachers found that it was very difficult to convert Javanese to Islam, unless a process of inculturation would be initiated. This decision proves to be the perfect step, as the Javanese start to consider Islam as a force that respects their local customs. The interaction that follows has transformed Javanese society and vice versa. Islam trans- forms Javanese society and Javanese society transformed Islam. In this article, the author presents some historical facts as back grounds, how the Javanese cultures has developed under the influence of different religious believes: Hinduism, Buddhism, local believes and Islam. This interaction forms a new model of culture which very much influences modern Javanese society. What remain intact is the spirit of mysticism. Contrast to the missionary character to Islam, Javanese society accepts Islam but also maintain the spirit of mysticism. Using the